2012
DOI: 10.1038/bjc.2012.382
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-214 modulates radiotherapy response of non-small cell lung cancer cells through regulation of p38MAPK, apoptosis and senescence

Abstract: Background:Radio- and chemotherapy (RT/CT) resistance hampers success in combating small and non-small cell lung cancers (SCLC/NSCLC). The underlying molecular mechanisms of RT/CT resistance of LCs are multifactorial and have been understood in part hitherto. miRNAs, key regulators of mRNAs, are well-recognised oncomirs; however, their role in regulating RT response remains poorly understood.Methods:Six human NSCLC and five SCLC cell lines with different SF2 values were investigated. Using microarray we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 57 publications
3
70
0
1
Order By: Relevance
“…p38 MAPK could promote apoptosis of lung adenocarcinoma cells via the regulation of the expression of the apoptosis-related proteins Bax and Bcl2 (29). The downregulation of p38 MAPK could reverse the radiotherapy resistance caused by the overexpression of miRNA (30). The present study found that after FANCD2 was silenced by shRNA interference, the expression of the p38 protein in the cells of the experimental group was decreased, while the expression of the p-p38 protein was increased compared with the expression in the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK could promote apoptosis of lung adenocarcinoma cells via the regulation of the expression of the apoptosis-related proteins Bax and Bcl2 (29). The downregulation of p38 MAPK could reverse the radiotherapy resistance caused by the overexpression of miRNA (30). The present study found that after FANCD2 was silenced by shRNA interference, the expression of the p38 protein in the cells of the experimental group was decreased, while the expression of the p-p38 protein was increased compared with the expression in the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…There were also several studies showing that miRNAs were associated with radiosensitivity in lung cancer. Radiotherapy response of lung cancer cells was modulated by miR‐214 through regulation of p38 MAPK, apoptosis, and senescence 19. The radiosensitization of lung cancer cells was induced by miR‐122 via targeting BCL‐W and IGF1R 59.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, one miRNA regulates multiple targets and could be regulated by multiple genes 13. It has been reported that miRNAs are involved in tumorigenesis, cell cycle, cell proliferation, apoptosis, tumor microenviroment, and radioresistance, acting as tumor suppressors or tumor promoters 14, 15, 16, 17, 18, 19, 20. It has also been verified that miRNAs are related to biological characteristics of cancer stem‐like cells, such as self‐renewal, proliferation, invasion, and radiotherapy or chemotherapy resistance 21, 22…”
Section: Introductionmentioning
confidence: 98%
“…The targets of miR-199a, V-Ki-Ras2 Kirsten rat sarcoma viral oncogene homolog and mitogen-activated protein kinase kinase 4 have been identified (28)(29)(30)(31), and the inhibitory effects of miR-199a and/or miR-214 on the expression of these target genes have been demonstrated (31). miR-199a and miR-214 may have important roles in cell growth and proliferation via the mitogen-activated protein kinase pathway (31,32).…”
Section: Discussionmentioning
confidence: 99%